CULTURAL AWARENESS IN EFL PEDAGOGY: A SCOPING REVIEW - Nofyan Fajry Amaruna; Siti Tarwiyah (Universitas Islam Sumatera Utara (UISU), 2026)
This scoping review maps 25 studies (2021–2025) on cultural awareness integration in English as a Foreign Language (EFL) contexts using Arksey and O'Malley's framework. Analysis identified four central themes: materials and curriculum representation, teacher beliefs and practices, learner perceptions and outcomes, and pedagogical strategies. Findings reveal persistent implementation challenges across all themes. Textbook analyses revealed systematic Western bias, with 70% of cultural content emphasizing target-culture contexts versus 30% local contexts. Teacher studies disclosed significant gaps between stated beliefs and classroom practices, which remained incidental rather than systematic. Learner research demonstrated positive attitudes toward intercultural learning, yet showed limited competence beyond familiar cultural contexts. Methodologically, databases searched included ERIC, Scopus, and Google Scholar using keywords including